Poetics of Antonyms in the groups of pomes Ibn Zaqaq Al-Balansi - Abd Attia, Bushra (Al-Adab Journal, 2021)
Based on this aesthetic that opposing dualities give to the poetic text, my choice was the subject of contradiction in the poet of the Andalusian poet Ibn Al-Zuqaq Al-Balansi. In the first axis, I dealt with the study of linguistic contradiction, and in the second axis the study of stylistic contradiction, and in it I stood upon the poet’s employment of the contrast structure that is based on the style and the linguistic context.The research has shown that the Andalusian poet was keen to explain his texts in the bad arts, especially the contradiction, and the art of the poet Ibn Al-Zuqaq Al-Balansi emerged in his care to achieve proportionality between opposites and to ensure the appropriate arrangement for them. And he used it to be a way to enhance the meaning, intensify the connotation, draw the image and influence the recipient, not just a verbal aesthetic artistic tool.